Multistakeholder Collaboration in Green Open Space Policy Policy Partnership Perspective Study in Sumenep - Ida Syafriyani; Unsul Abrar; Wilda Rasaili (Ilomata International Journal of Social Science, 2026)
Jakarta, as a metropolitan city rich in history and culture, offers substantial potential for community-based tourism development through walking tours. The quality of tourist experiences is closely associated with the competence of tour guides, which is reflected in their education, certification, motivation, and professional performance.  This study examines the relationships between education and certification with motivation and their associations with the performance of the Jakarta Good Guide walking tour community. Data were collected from 32 respondents and analysed using Partial Least Squares–Structural Equation Modelling (PLS-SEM).  The results indicate that education is positively and significantly associated with motivation (β = 0.803; p < 0.001), whereas certification is not significantly associated with motivation (β = 0.022; p = 0.870). Motivation shows the strongest association with performance, as indicated by the largest path coefficient in the model (β = 0.850; p < 0.001). Furthermore, motivation mediates the relationship between education and performance within the tested model (β = 0.683; p < 0.001). In contrast, certification does not demonstrate significant direct or indirect associations with performance. These findings highlight the role of motivation as a key mechanism linking education and performance within this sample. From a practical perspective, the study suggests that community-based tourism development programs may benefit from prioritizing educational initiatives and motivational enhancement rather than relying solely on formal certification processes.